Privacy and Social Spaces - Da Silva Perez, Natália (TSEG - The Low Countries Journal of Social and Economic History, 2021)
In this introductory text to the special issue Regulating Access: Privacy and the Private in Early Modern Dutch Contexts, Natália da Silva Perez argues that privacy can be a productive analytical lens to examine the social history of the Dutch Republic. She starts by providing an overview of theoretical definitions of privacy and of the ‘private versus public’ dichotomy, highlighting their implications for the study of society. Next, she discusses the modern view of privacy as a legally protected right, explaining that we must adjust expectations when applying the concept to historical examination: in the early modern period, privacy was not yet fully incorporated within a legal framework, and yet, it was a widespread need across different echelons of society. She provides a historical overview of this widespread need for privacy through instances where people attempted to regulate access to their material and immaterial resources. Finally, she describes how the four articles in this special issue contribute to our understanding of the role of privacy in early modern Dutch life.